GROUND SEALING EQUIPMENT ON THE BASIS OF HYDRAULIC IMPACT DEVICES - N. S. Galdin (Вестник СибАДИ, 2017)
A tamping – an effective way of soil compaction. At a tamping the ground is dabed at the expense of a tool impact energy. Hinged ground sealing the equipment to excavators hydrostamps on the basis of hydraulic impact devices are perspectiv. Data about ground sealing equipment on the basis of hydraulic impact devices are resulted. Power indicators (energy, capacity of individual blow) hydropneumatic impact devices depend on speed mobile part and its such design data, as weight, course size mobile part, pressure of gymnastics of gas of the pneumoaccumulator. Dependences of mass of loose ports and an impact energy from width of a dabed surface soil and contact voltages on a ground surface are presented.